Pengaruh Engagement Rate, Kepuasan Pengunjung, dan Customer Experience Terhadap Minat Berkunjung di Museum Geologi Bandung: Penelitian - Shafira Azkia Syawaliyah; Riyandi Nur Sumawidjaja; Dadan Abdul Aziz Mubarok; Erna Herlianawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The purpose of this study is to ascertain how visitors' intentions to visit the Geological Museum of Bandung are influenced by social media engagement rate, visitor satisfaction, and customer experience. The study is predicated on evolving post-pandemic tourist behavior, variable visitor numbers, and disparities in the efficacy of involvement across digital channels. People who have visited the museum were given questionnaires as part of a quantitative approach. Multiple linear regression, validity tests, reliability tests, and hypothesis testing were used to process the data. The findings show that visit intention is positively and significantly impacted by engagement rate, visitor satisfaction, and customer experience, both separately and collectively. In order to boost public interest, our findings highlight the significance of increasing visitor experiences, enhancing digital communication tactics, and improving service quality.